Public Sector Leadership and Organizational Change: Analyzing the Effectiveness of Transformational Leadership in Government Agencies - Maolani, Dedeng Yusuf (JOM, 2023)
This study examines the effectiveness of transformational leadership in driving organizational change within government agencies. Transformational leadership, characterized by the ability to inspire and motivate employees towards a shared vision, is increasingly recognized as vital for public sector reform and improved organizational performance. Through a comprehensive literature review and in-depth case studies of selected government agencies, this research identifies key transformational leadership practices and their impact on organizational change initiatives. The findings reveal that transformational leaders in the public sector play a crucial role in fostering a culture of innovation, collaboration, and adaptability, which are essential for successful change management. Additionally, the study highlights the challenges and barriers faced by public sector leaders in implementing transformational leadership and provides policy recommendations to enhance leadership effectiveness. By contributing to the understanding of leadership dynamics in the public sector, this research offers valuable insights for policymakers and public sector leaders aiming to navigate the complexities of organizational change.